Confucius Institute, Belt and Road Initiative, and Internationalization - Hao Wang; Yonghui Han; Jan Fidrmuc; Dongming Wei (Center for Economic Studies and Ifo Institute (CESifo), 2020)
In this paper, we study the role of Confucius Institute in supporting internationalization of Chinese enterprises. Employing a panel dataset containing 66 Belt-Road countries and 75 non Belt-Road countries from 2006 to 2017, we find that the Confucius Institute has had a positive effect on Chinese CMA in general and that this effect has become stronger in Belt-Road countries after the Belt and Road Initiative was launched in 2013. Our results suggest that the earlier the host country joins the Belt and Road Initiative, the stronger is the interactive effect of CI and Belt and Road Initiative. Moreover, we show that the Confucius Classroom, a related program, also positively affects Chinese CMA in the context of the Belt and Road Initiative. These findings are robust to controlling for endogeneity and sample selection biases.
Keywords: F23; Z10; 330; cultural institute; institutions; cultural distance; Belt and Road Initiative; Confucius Institute; cross-border mergers and acquisitions